Penerapan Arsitektur Berkelanjutan pada Bangunan Komersial & Pariwisata sebagai Upaya Mewujudkan Kota Hijau - Bahari, Puspita Indah; Zuhri, Syaifuddin (Universitas Medan Area, 2024)
The phenomenon of climate change impacts is starting to be seen in almost all countries in the world. The contribution of green cities is very impactful in overcoming the phenomenon of mitigating the effects of global warming. A green city is a city that prioritizes environmental balance that seeks to create comfort for city residents and visitors (Yunus, 2012). One of the development methods with regard to environmental sustainability for planned and built ecosystems, is a strategy to reduce adverse impacts on the environment during the development process by prioritizing efficiency and wisdom in using materials, energy, and space management. This article focuses on deepening the application of sustainable architectural design in an effort to realize a green city. The research is conducted on several applications of architectural design of commercial and tourism buildings that apply sustainable architecture. This effort is made to realize a green city environment through sustainable architecture applied to buildings and their environment. Using descriptive - qualitative method by examining the sustainable aspects that arise in the building.